3D‐Printed Autonomous Sensory Composites. Issue 3 (4th January 2017) - Sundaram, Subramanian; Jiang, Ziwen; Sitthi‐Amorn, Pitchaya; Kim, David S.; Baldo, Marc A.; Matusik, Wojciech
Abstract : A method for 3D‐printing autonomous sensory composites requiring no external processing is presented. The composite operates at 1.5 V, locally performs active signal transduction with embedded electrical gain, and responds to stimuli, reversibly transducing mechanical strain into a transparency change. Digital assembly of spatially tailored solids and thin films, with encapsulated liquids, provides a route for realizing complex autonomous systems.